Price Perception, Product Quality, and Electronic Word of Mouth (e-WOM) Increase Purchasing Decisions at Pizza Marzano - Laluna Aprilla Simamora; Parlagutan Silitonga (Asosiasi Riset Ilmu Manajemen Kewirausahaan dan Bisnis Indonesia, 2025)
This study aims to determine the influence of price perception, product quality, and electronic word of mouth (e-WOM) on consumers’ purchase decisions in the culinary industry. A quantitative method was employed, with a population consisting of consumers who have made purchases. Data were obtained through questionnaires distributed to 250 respondents using an accidental sampling technique. Data were analyzed using the Structural Equation Model (SEM) via SmartPLS 3.0 software. The results show that two independent variables, namely price perception and e-WOM, significantly influence consumer purchase decisions. This indicates that restaurants offering lower prices while maintaining high product quality are more likely to attract consumers. Moreover, customer experiences shared through online reviews can influence potential buyers in their future purchasing decisions. The findings of this study are expected to serve as a reference for culinary business practitioners in developing more effective marketing strategies. Future research may consider including other variables that could further enhance purchase decisions effectively. Keywords: Electronic Word of Mouth (e-WOM); Purchase Decision; Product Quality; Price Perception